Social tension and violence in the development debate - Singh, Sujata (2002)
Social tension and violence lie at the core of the development debate. During the 1950s and 1960s, the pace of development in newly emerging independent countries was held responsible for the growing tension and violence in these societies. However, developments in the West took this debate a step forward to look into deeper problems. An attempt has been made in this article to analyse the theoretical underpinnings of the development debate and their implications for the future. The author examines the views of leading development theorists who were instrumental in creating a powerful world-view of the developing countries. - Reproduced.
Keywords: Violence; Economic and social development; Social conflicts